Revisioning the possible: aligning blended IL instruction with principles of EBP for meaningful nursing instruction - Nelson, Jody; Foster, Ali; Asirifi, Mary; Gates, Melanie; Su, Wanhua; Velupillai, Nirudika (My University, 2021)
The MacEwan BScN program supports development of skills and attributes in the domain of clinical practice, including information literacy (IL) interventions in Year 2. Addressing a noticeable trend in 2018 of fewer students making connections between IL and evidence-based practice (EBP), librarians and instructors collaborated on an IL redesign, integrating IL and EBP in a blended learning (BL) context. The redesigned IL intervention, which pulls from best practices in online EBP instruction in nursing (Kelly et al., 2016), was implemented in 2019 with revised learning outcomes. Literature on IL instruction and EBP learning points to similarities, synergies, and value of a more fulsome integration in teaching (Adams, 2012; Amit-Aharon et al., 2020). While Adams (2012) emphasizes the importance of teaching IL concepts through a disciplinary lens, Amit-Aharon et al. (2020) note the significant positive correlation between IL self-efficacy, EBP attitudes and knowledge, and future EBP implementation in practice. Purpose: This Scholarship of Teaching and Learning (SoTL) research investigates the impact of the redesigned BL IL intervention on YR 2 nursing students’ perceived EBP confidence, attitudes, and ability, using an adapted Student EBP Questionnaire (S-EBPQ) (Upton et al., 2016).
Presented June 8-11, 2021, at CHLA (Canadian Health Libraries Association) 2021 held at Winnipeg, MB.
Keywords: information literacy; evidence-based practice (EBP); nursing students